Review Of The Collateral Valuation Procedures By The Internal Appraisal In Loan Disbursement At PT. Pasar Dana Pinjaman (Danamas) - Larasati, Dinda; Sudradjat, Sudradjat (Program Vokasi dan LPPM IBI Kesatuan, 2023)
Collateral is an asset or property provided by the borrower to the lender in order to obtain the loan facility. Collateral is one of the most important things in lending because of its role as the second way out when the default of event occurs in a loan. Therefore, a division and special work procedures are needed to asses the feasibility of an object to be used as collateral. This review was conducted to find out the characteristics of assessable assets that can be financed and used as a collateral by PT. Pasar Dana Pinjaman, as well as to identify the collateral appraisal procedures by internal appraisal, and obstacles faced during the collateral appraisal process. The result of this review show that assets that can be used as collateral are non-movable tangible assets with marketable value, no over-financing, and free from disputes (can be legally bound). Considering the capacity of internal appraisal, collateral that can be appraised by the internal appraisal are those that meets the following criteria, which is total exposure below IDR 10 billion, located within a maximum radius of 30 km from the operational office, classified as a simple property, and there are no negative lists around them. Based on the results of the review of the collateral appraisal procedure by internal appraisal at PT. Pasar Dana Pinjaman, it can be conclude that the internal appraisal division has a systematic procedure in place which is include in the internal appraisal SOP and is in compliance with the standards set by MAPPI, from order acceptance to assessment report. Obstacles faced by the internal appraisal division during the appraisal process are the difficulties of finding comparable data, hard-to-reach Person In Charge, and indications of fraud during appraisal process.